High incidence of brain and other nervous system cancer identified in two mining counties, 2001–2015. (February 2020) - Zhang, Yanan; McDermott, Suzanne; Davis, Bryn; Hussey, James
Highlights: When comparing age group specific incidence rate ratio (IRR) for DL/SB versus comparison counties, we found an IRR for DL/SB of 6.28 for children ages birth to 4 years, and an IRR of 3.95 for adults age 30-34 years. Brain and other nervous system cancers incidence for residents of DL/SB ages 0-4 years is 1.54/10, 000 person years compared to 0.24/10, 000 person years in the remaining counties in Montana. Similarly, incidence of brain and other nervous system cancer for residents of SB/DL aged 30-34 years is 1.84/10, 000 person years compared to 0.47/10, 000 person years. Further research is needed to explore associations between metal exposures and brain and other nervous system cancers, that includes residential history, exposure to radiation, family history of conditions associated with brain and nervous system cancer, and other known risk factors. Abstract: Two counties in Montana, Deer Lodge and Silver Bow (DL/SB), have two Superfund sites, as well as an active copper and molybdenum mine in SB. The population living in proximity to these sites are exposed to additional metals and some have been shown to be neurotoxic, especially for children; thus, this study focused on the incidence of brain and other nervous system cancers. The Montana Central Tumor Registry data was used to identify the cases in DL/SB and the remaining 54 counties of Montana (comparison group). After controlling for sex, cancer stage, and year of diagnosis, we found an incidence rate ratio for DL/SB versus comparison group of 6.28 (95% CI: 2.32–17.02) for children ages birth to 4 years, and 3.95 (95% CI: 1.66–9.38) for adults age 30–34 years. The high incidence rate of the brain cancer in the two age groups requires public health action.